Constitutional control as a factor of market economy maintenance - Dochev, M.; Dochev, H. (Економічний вісник Донбасу, 2010)
After the change of the social-political system in Bulgaria during the last decades of the XX century, Bulgaria has been facing a great number of difficulties in the transition from planned to market economy. The adoption of a new democratic Constitution has to do with the introduction of new functions of state authorities and the standing for new principles. The subject of this report is the activity of the Constitutional Court (CC) and its role in the enforcement of the basic principle of the market economy in accordance with the Bulgarian basic law the free business initiative. Key words: Constitutional Court, constitutional control, free business initiative, competitiveness, monopoly, consumer protection. Після зміни соціально-політичної системи в Болгарії протягом останніх десятиліть ХХ століття, Болгарія стикається із численними труднощами при переході від економіки планової до ринкової. Ухвалення нової демократичної Конституції має відношення до введення нових функцій державних властей і підтримки нових принципів. У статті розглянута діяльність Конституційного Суду та його роль в здійсненні основного принципу ринкової економіки відповідно до Болгарського основного закону - вільна ділова ініціатива. Ключові слова: Конституційний Суд, конституційний контроль, ділова ініціатива, конкурентоспроможність, монополія, захист споживача. После изменения социально-политической системы в Болгарии в течение последних десятилетий ХХ столетия, Болгария сталкивается с многочисленными трудностями при переходе от плановой к рыночной экономике. Принятие новой демократической Конституции имеет отношение к введению новых функций государственных властей и поддержки новых принципов. В статье рассмотрена деятельность Конституционного Суда и его роли в осуществлении основного принципа рыночной экономики в соответствии с Болгарским основным законом — свободная деловая инициатива. Ключевые слова: Конституционный Суд, конституционный контроль, свободная деловая инициатива, конкурентоспособность, монополия, защита потребителя.